Effect of type of meat and storage on the quality of pre-cooked patties - REDDY, K PRABHAKAR; RAO, T S (The Indian Journal of Animal Sciences, 2013)
Patties were prepared by utilizing the meat from spent layers and ducks separately. The pre-cooked patties were stored at 5+-1Â° C for 6 days and evaluated for quality. Patties made with chicken meat had (P<0.05) higher per cent cooking loss. total ash colour and flavour scores, whereas patties of duck meat recorded higher values of gain in thickness, TBA values. per cent moisture content, tenderness,juiciness and overall acceptance scores. Regardless of type of the meat. refrigerated storage of pre-cook cd patties for 6 days resulted in (P<0.05) less gain in thickness and higher cooking loss. more shrinkage in diameter and higher pH and TBA values and reduction in crude protein and ether extract levels. Storage had no effect on the organeloptic scores of pre-cooked patties except on colour.